Polysemy Found in Sir Alex Ferguson Interview on Beanyman Sport - Muhammad Azmi Bahari; Ervina CM Simatupang (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
Polysemy is a type of lexical relation which refers to a word that has more than one meaning. The word polysemy comes from the Greek word poly- which means "many" and -sệma which means "signs". According to Nordquist (2019), polysemy is an association of one word with two or more distinct meanings. Meanwhile, Hasa (2016) defined polysemy as words or phrases with different, but related meanings. This study aims to analyze polysemy words found in Sir Alex Ferguson’s interview by explaining the exact meaning of those words. The method used in carrying out the study was descriptive analysis which concerns describing the meanings of polysemy words found. Then, the data used for this study was taken from a Youtube video entitled "Sir Alex Ferguson Full Length Interview (Fergie Time, Van Gaal & Developing Players)" from the BeanymanSports Youtube channel. The data analysis process began by identifying the polysemy words in Sir Alex Ferguson’s interview using Oxford Advanced Learner's Dictionary. After the polysemy words on that video are found, there are explanations about those words using two different points of view. The first is explained in terms of general meaning, and another one is explained in terms of context meaning. Then, the meaning of those words is categorized into two types: polysemy words related to football terms, and polysemy words related to general terms. From this study, it can be concluded that polysemy words can be found not only in a written form source but also in a speech or interview form.